If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -1) + 4 = -20 Reorder the terms: 2(-1 + 3x) + 4 = -20 (-1 * 2 + 3x * 2) + 4 = -20 (-2 + 6x) + 4 = -20 Reorder the terms: -2 + 4 + 6x = -20 Combine like terms: -2 + 4 = 2 2 + 6x = -20 Solving 2 + 6x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6x = -20 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = -20 + -2 6x = -20 + -2 Combine like terms: -20 + -2 = -22 6x = -22 Divide each side by '6'. x = -3.666666667 Simplifying x = -3.666666667
| 1+3x=8a+6 | | 15.95=3.19 | | 2(8y-11)-7=147 | | g+11=9 | | 20-3x-2x= | | 8y+x=13x+20 | | 2(x-y)+3(x-y)= | | 9x+8.32=7x+11 | | 6x-2+4=-20 | | 19/5=5k/5 | | -5.8+1.1x=4.5 | | 123=3x-3 | | 3x+2=2[2x+1] | | 12.85=x-4.34 | | 2-3/8=13 | | 5+.25m=50 | | -6=10p/7 | | 6-3p=-0 | | 4x-5=2x+4 | | 12z^2-7z+6=0 | | 60x^3-390x=0 | | 5u=45 | | y=9lnx^3 | | 5[x+1]=20 | | 3z+2z=5z | | 30=a | | 5x-10t=3 | | 8x^2+5=517 | | 3(x+4)+2(x+2)=41 | | 6b+18=7b+-21 | | 3b-24b= | | 5(5m-4)+11=66 |